Pengembangan Rancangan Pelaksanaan Pembelajaran (RPP) Berbasis Model Inside Outside Circle (IOC) Untuk Meningkatkan Prestasi Belajar Siswa - Muhamad Khoirur Roziqin; Muhammad Alwi Fajar (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2022)
The lesson plan can be used as a reference in teaching and learning activities in the classroom and as a medium for improving the quality of teachers to meet competency standards, namely mastery of knowledge, skills, and attitudes. Therefore, researchers developed a learning implementation plan based on the Inside Outside Circle (IOC) model which was deemed very suitable to assist in student learning activities in improving student learning outcomes. This type of research uses a Research and Development (R&D) approach. This research was conducted using the Borg & Gall (1983) development model which was modified into three stages of development, namely preliminary studies, product design, and development and evaluation stages. The results of the study showed that the lesson plan that we proposed was declared suitable for use without revision. Aspects of the validity of the implementation of the learning implementation plan in terms of the assessment of two material experts with an average of 4.38 and student responses to the Learning Implementation Plan (RPP) with the Insite Outsite Circle (IOC) learning model with an average response of 91.88% and learning achievement students who are taught the Inside Outside Circle (IOC) learning model produce better grades. The aspect of effectiveness seen from the results of the posttest students reached an average value of 83.75.